An Analysis the Cloud-Based E-Learning and types of Learning Disability: Examining the Impact of Cloud-Based E-Learning on Learning Disabilities in Rural Areas (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Education is important aspect of every person’s life and no anyone can improve their ability andinnovative skill without education. Now days in rural area student faced many hurdle in their educationallife such as, lack of infrastructure, lack of E-learning facility, long distance of school, old method ofteaching. This all kinds of problem influence on student learning ability and interest. Another problem inlearning process is learning disabilities, in propose research we examine two types of learning disabilitiesinfrastructural and neurological this both disabilities are not present in handicapped categories and thislearning disabilities mostly present in rural student due to lack of facility and educational environment.Cloud computing is internet based technology use to provide resources and application on demand.Student can access and utilizes cloud resources anywhere any time using their own devices like laptop,mobiles, and tablets.